Understanding the Dominant Moisture Sources and Pathways of Summer Precipitation in the Southeast Prairie Pothole Region. Issue 3 (1st March 2022) - Abel, Benjamin D.; Rajagopalan, Balaji; Ray, Andrea J.
Abstract: Summer rainfall in the southeast Prairie Pothole Region (SEPPR) is an important part of a vital wetland ecosystem that various species use as their habitat. We examine sources and pathways for summer rainfall moisture, large‐scale features influencing moisture delivery, and large‐scale connections related to summer moisture using the Hybrid Single‐Particle Lagrangian Integrated Trajectory (HYSPLIT) model. Analysis of HYSPLIT back trajectories shows that land is the primary moisture source for summer rainfall events indicating moisture recycling plays an important role in precipitation generation. The Great Plains Low‐Level Jet/Maya Express is the most prominent moisture pathway. It impacts events sourced by land and the Gulf of Mexico (GoM), the secondary moisture source. There is a coupling between land, atmosphere, and ocean conveyed by large‐scale climate connections between rainfall events and sea surface temperature (SST), Palmer Drought Severity Index, and 850‐mb heights. Land‐sourced events have a connection to the northern Pacific and northwest Atlantic Oceans, soil moisture over the central U.S., and low‐pressure systems over the SEPPR. GoM‐sourced events share the connection to soil moisture over the central U.S. but also show connections to SSTs in the North Pacific and Atlantic Oceans and the GoM, soil moisture in northern Mexico, and 850‐mb heights in the eastern Pacific Ocean. Both types of events show connections to high 850‐mb heights in the Caribbean which may reflect a connection to Bermuda High. These insights into moisture sources and pathways can improve skill in SEPPR summer rainfall predictions and benefit natural resource managers in the region. Key Points: Land is the primary source of moisture for all summer rainfall events in the southeast Prairie Pothole Region (SEPPR) The Great Plains Low Level Jet/Maya Express is the primary pathway of moisture delivery for land and Gulf of Mexico sourced events Insights from this work can improve the skill of SEPPR summer rainfall predictions which would be useful to resource managers in the region